1990
DOI: 10.1038/ki.1990.39
|View full text |Cite
|
Sign up to set email alerts
|

Transport of organic compounds in renal plasma membrane vesicles of cadmium intoxicated rats

Abstract: Effects of cadmium intoxication on renal transport systems for various organic compounds were studied. Subcutaneous injections of CdCl2 (2 mg Cd/kg.day) for two to three weeks induced marked polyuria, glycosuria, and proteinuria without altering glomerular filtration rate. In renal cortical brush border membrane vesicles (BBMV) isolated from cadmium treated rats, Na(+)-dependent D-glucose uptake was markedly attenuated, and this was due to reduction in Vmax and not Km. Likewise, Na(+)-driven L-glutamate transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…The Na+-gradient-driven uptake in control vesicles was slightly above the equilibrium for [35S], and twofold and sixfold above equilibrium for [3Hi-glucose and [32p], respectively. In accordance with recent findings by Lee et al [19,20], BBMV from Cd-treated rats exhibited a much lower overshoot for glucose, thus indicating a significant decrease of the Na+-glucose cotransport in these membranes. In contrast, Na+-sulphate cotransport was not inhibited.…”
Section: Bbmv and Enzymessupporting
confidence: 92%
See 3 more Smart Citations
“…The Na+-gradient-driven uptake in control vesicles was slightly above the equilibrium for [35S], and twofold and sixfold above equilibrium for [3Hi-glucose and [32p], respectively. In accordance with recent findings by Lee et al [19,20], BBMV from Cd-treated rats exhibited a much lower overshoot for glucose, thus indicating a significant decrease of the Na+-glucose cotransport in these membranes. In contrast, Na+-sulphate cotransport was not inhibited.…”
Section: Bbmv and Enzymessupporting
confidence: 92%
“…The Cd-treated rats exhibited 3.6-fold higher urine flow and excreted 3 times more urine, 5 times more urine protein and 40% more Pi in the urine. These findings, being typical for chronic Cd intoxication, are similar to those previously published for rats that underwent similar treatment with Cd [2,[17][18][19].…”
Section: Renal Functionssupporting
confidence: 91%
See 2 more Smart Citations
“…Other metals, such as, Cd inhibit Na-D-glucose transporter 24) in the rat small intestine brush border membrane, the L-alanine 25) and L-glutamate 26) cotransporter system in the rat renal brush border membrane, and mercury also inhibits the Na + -Pi-cotransporter 27) . In our previous studies, cadmium 28) , inorganic mercury 29) , platinum 30,31) and vanadium 32) were found to inhibit the citrate uptake in a concentration-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%